Import substitution Impact on Growth of Production of Mineral Products and Metallurgy: shortTerm and long-Term Forecasting of basic sectors of the National Economy - E. A. Fedorova; A. R. Nevredinov; K. S. Melikhov; A. I. Yashchenko (Финансы: теория и практика, 2023)
The purpose of the study is to identify ways of short- and medium-term development of mineral production and metallurgy in the Russian Federation in the context of the policy of sanctions based on economic and mathematical modeling. The impact of sanctions on production in the basic sectors of the Russian economy, as well as the impact of import substitution on production in the short- and long-term is investigated. The research methodology includes panel regression with fixed effects and Bayesian vector autoregression (BVAR model). The sanctions index is calculated based on a sentimental analysis of the texts of news publications. This index is based on the results of computer analysis of a set of thematic texts (evaluation of the frequency of words and phrases, correlation analysis, case analysis based on the BERT neural network). The paper demonstrates the importance of an industry-specific approach to the implementation of import substitution policy in view of its time horizon. For example, for the mineral products industry, the current import substitution policy can be considered effective in terms of the production index forecast, and for the metallurgical industry, the import substitution policy needs to be revised, since a sharp decline is expected in the short-term when the baseline scenario is implemented, and in the long-term production stabilizes without showing growth. As a result, the efficiency of the import substitution policy is considered to be completely dependent on the industry in which it is implemented. Fund intensity and other factors affecting industry cycles must be considered in order to forecast policy results. Import substitution also has a long-term positive impact.